Minimal Model to Investigate Visco-Elastic Contact Effect on Friction-Induced Vibration and Squeal - Niknam, Alborz; Farhang, Kambiz (Journal of Applied Nonlinear Dynamics, 2026)
A well-known 2-DOF mass-on-belt model is used to investigate friction-induced vibration. By employing a Kelvin-Voigt definition to simulate viscoelastic contact interface, effects of contact modeling on the stability of a linearized system and sustain vibrations of the nonlinear system, such as stick-slip and contact detachment are studied. In addition, the effect of a hardening nonlinear contact stiffness on transient and steady-state system responses has been discussed. Horizontal friction force is a function of vertical displacement and velocity through viscoelastic definition of contact. Contact detachment, where friction force disappears, is another source of nonlinearity and considered in governing equations. Eigenvalue analysis is performed to show the effect of viscoelastic/nonlinear contact on the stability of a linearized system. Numerical analysis is employed to solve Filippov systems of equations of motion with different possible phases in a cycle, i.e. slip, stick and separation. Results show that viscoelasticity at the contact interface plays a crucial role in the local stability of the linearized system and vertical sustained oscillation.